Population Genetic data for 15 Autosomal STR markers in Eastern Turkey - Tokdemir, Mehmet; Tuncez, Ferhat Turgut; Vicdanli, Nazif Harun (Elsevier Science Bv, 2016)
The allelic frequency distribution and statistical genetic parameters of forensic relevance for 15 STR loci (D8S1179, D21S11, D7S820, CSF1PO, D3S1358, TH01, D13S317, D16S539, D2S1338, D195433, vWA, TPOX, D18S51, D5S818 and FGA) in a population sample of 802 unrelated individuals in Eastern Turkey. The expected performance of these loci for personal identification and paternity testing in this population was estimated. Eastern Turkey and other 12 country population data were compared using allele frequencies. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Short tandem repeats; Turkey population; Allele frequencies; DNA typing